Clinical presentation of hypothyroidism: a study of 50 cases - Hanif, M. Abu; Hoque, A. K. M. Aminul; Habib, Ahsan; Islam, Hasanul; Hossain, Amjad; Al Adilujjaman, Al Fatah (International Journal of Research in Medical Sciences, 2022)
Background: When the thyroid gland does not produce and release enough thyroid hormone into your circulation, it is known as hypothyroidism. Your metabolism becomes slower as a result. Hypothyroidism, also known as an underactive thyroid, can make you feel exhausted, put-on weight, and have trouble with cold weather. In utero, throughout infancy, during youth, or even during maturity, it may begin to develop. The frequency of unanticipated overt hypothyroidism varies from 1 to 18 cases per thousand persons when accompanied by biochemical and clinical symptoms of hypothyroidism. The aim of the study was to observe the various clinical presentations of hypothyroidism Methods: This cross-sectional observational case-based study was conducted at the institute of nuclear medicine, Dhaka medical college hospital, Dhaka, Bangladesh. The study duration was 6 months, from January 2005 to July 2005. A total of 50 patients attended at the study place during the study period who were biochemically hypothyroid were included in the study. Results: The age range of the patients was 13 months to 54 years with a mean age of 29.5 years in this series. The majority of the patients were between 20 to 49 years of age. Female comprises 80.0% in comparison to 20.0% of male cases of hypothyroidism. Spontaneous primary (idiopathic) hypothyroidism (90.0%), post-radioiodine therapy, and post-ablative hypothyroidism were the most important causes of hypothyroidism in this series. Most typical symptoms and signs of hypothyroidism were found in this study. The most common symptoms were generalized weakness, lethargy, slowness of activities, impairment of memory, loss of scalp hair, somnolence, dry skin, puffiness of the face, constipation, weight gain, hoarseness of voice, swelling of the body, decreased sweating and paraesthesia. Cases of idiopathic hypothyroidism and other types had similar symptoms. The mean duration of symptoms before medical consultation was 2.9 years. Dry and coarse skin topped the list of physical findings and was present in 60.0% of the cases. Other findings in order of frequency include goiter (56.0%), puffiness of the face (38.0%), cold and thick skin (44.0%), thick tongue (24.0%), peripheral edema (24.0%), Anemia (20.0%), pallor of the face (12.0%), bradycardia (08.0%), thick lips (4.0%), ascites (2.0%) and pericardial effusion (2.0%). Conclusions: Although in the present series a limited number of patients were included, it encompassed varieties of cases. Moreover, an attempt was made to evaluate the common presentation, age incidence, sex distribution, and laboratory status of hypothyroidism in our country, giving more emphasis on clinical findings.